2009
DOI: 10.1177/0267659109354656
|View full text |Cite
|
Sign up to set email alerts
|

Safe time limits of aortic cross-clamping and cardiopulmonary bypass in adult cardiac surgery

Abstract: XCT and CPBT are predictors of immediate postoperative morbidity and mortality. In our experience, cardiac procedures with CPBT<240 min and XCT<150 min were associated with a rather low risk of immediate postoperative adverse events independently of the complexity of surgery patient's operative risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 14 publications
7
95
3
3
Order By: Relevance
“…Contrary to the findings of other studies, however, the incidence of post-operative myocardial infarction (PMI) was higher in trainee cases (1.1% vs. 0.3%, p = 0.008) [6,16]. This may reflect the longer perfusion and aortic cross-clamp time in trainee cases, which have been previously shown to be risk factors for PMI [25]. Nevertheless, the incidence of PMI in the trainee group is comparable to that reported in many other studies and it may represent a chance finding given that the overall incidence of PMI in the current study was low at only 0.4% [6,16,26].…”
Section: Discussioncontrasting
confidence: 64%
“…Contrary to the findings of other studies, however, the incidence of post-operative myocardial infarction (PMI) was higher in trainee cases (1.1% vs. 0.3%, p = 0.008) [6,16]. This may reflect the longer perfusion and aortic cross-clamp time in trainee cases, which have been previously shown to be risk factors for PMI [25]. Nevertheless, the incidence of PMI in the trainee group is comparable to that reported in many other studies and it may represent a chance finding given that the overall incidence of PMI in the current study was low at only 0.4% [6,16,26].…”
Section: Discussioncontrasting
confidence: 64%
“…When a long-term stent graft is inserted, the risk of paraplegia and spinal cord injury must be considered due to extensive sacrifice of spinal arteries impairing collateral blood flow to the spinal cord, combined with inadequate protection during the operation (14). The longer cardiopulmonary bypass and cardiac arrest time, aortic cross-clamping time and cerebral perfusion time might inevitably be associated with post-operative cardiac and cerebral injury and organ dysfunction (25,(29)(30)(31)(32). In some cases, extending the initial surgery to total arch replacement might not be able to eliminate the entire dissection in the downstream aorta, e.g., at the level of coeliac trunk and iliac arteries (14).…”
Section: Discussionmentioning
confidence: 99%
“…4, 5 The aim of right anterolateral thoracotomy approach is to reduce the morbidity, short hospital stays, early discharge and short rehabilitation time. [5][6][7] A study conducted by Ganie et al (2013) comparing anterolateral thoracotomy against standard median sternotomy for mitral valve surgery and observed that the study populartions of both groups were comparable in terms of age, sex, NYHA class of heart failure and ejection fraction. 6 Thoracotomy shows better | Original | Article |…”
Section: Introductionmentioning
confidence: 99%